2009
DOI: 10.1080/00016340902971433
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal outcomes and four‐year follow‐up after spontaneous or iatrogenic preterm prelabor rupture of membranes before 24 weeks

Abstract: Pregnancy after iatrogenic PPROM had a better prognosis than after spontaneous PPROM. Intensive management with corticosteroids and antibiotics appeared to be helpful. Neonatal survival in spontaneous PPROM before 24 weeks remained very poor and discussing pregnancy termination in these cases seems legitimate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 19 publications
3
18
0
Order By: Relevance
“…Conservative management could be selected, but fetal prognosis remains poor in such cases. 5 Epidemiological, microbiological and clinical evidence suggests an association between infection and preterm birth. 4 Strategies for cases of preterm labor in which the presence of subclinical (silent) intrauterine infection, rather than overt intrauterine infection, is suspected may need to use not only tocolytic agents but also anti-inflammatory agents.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative management could be selected, but fetal prognosis remains poor in such cases. 5 Epidemiological, microbiological and clinical evidence suggests an association between infection and preterm birth. 4 Strategies for cases of preterm labor in which the presence of subclinical (silent) intrauterine infection, rather than overt intrauterine infection, is suspected may need to use not only tocolytic agents but also anti-inflammatory agents.…”
Section: Discussionmentioning
confidence: 99%
“…Normal vaginal pH varies between 4.4 and 6.0, whereas pH of amniotic fluid is 8.0 [18]. A manual vaginal examination should be contraindicated in the presence of PPROM because of its association with an increased risk of chorioamnionitis by ascending infection and reduction of the latency period by 9 days on average [21,73].…”
Section: Diagnosis Of Pprom Routine Diagnostic Proceduresmentioning
confidence: 99%
“…Monitoring of initial signs of infection is necessary (maternal and fetal heart rate, maternal body temperature and laboratory findings), when procedure-related leakage occurs, but in general, leakage of amniotic fluid after a sterile invasive procedure is less likely to result in an obstetrical problem compared to spontaneous PPROM. Prolongation of pregnancy beyond completion 34 weeks of pregnancy to reduce the risk of neonatal complication and demise has been reported following procedure-related PPROM [73,95,98,99], whereas labor induction is recommended following spontaneous PPROM after 34 weeks' gestation.…”
Section: Antibiotics and Probioticsmentioning
confidence: 99%
“…8 Despite advances in neonatal care and apparent improved neonatal outcomes, longer-term outcomes of children delivered following early PPROM are largely unknown. One small study 9 examined early childhood outcomes among 13 neonates who were expectantly managed following spontaneous PPROM at less than 24 weeks; 3 (23%) died in the hospital, and only 2 (15%) survived without obvious long-term morbidity at age 4 years. In another small study, Pristauz et al 10 reported that half of 12 infants surviving PPROM between 14.0 and 24.9 weeks had normal neurological and developmental outcomes at age 2 years.…”
mentioning
confidence: 99%